THREAT RHETORIC AND SECURITIZATION: us immigration policy in the Trump administration - Contrera, Flávio [UNESP]; Mariano, Karina Lilia Pasquariello [UNESP]; Menezes, Roberto Goulart (FapUNIFESP (SciELO), 2022)
This article aims to show that Donald Trump’s changes in US migration policy were driven by threat rhetoric with the purpose of securitizing immigration. Starting from the binomial “I-other” to analyze the Executive’s discourses and unilateral actions, we used the method of Critical Discourse Analysis (CDA) to identify the discursive strategies that mobilized the “us against them” debate. In line with the theoretical assumptions of the Copenhagen School, we argue that Trump built a movement to securitize migration policy by employing a narrative in which Latin Americans and Muslims represent a threat to Americans and the United States. However, we conclude that this movement was incomplete, as it did not engender legitimacy before most of public opinion, encountered resistance to its implementation in the Judiciary and in state governments and did not foster the forging of a consensus in the Legislative that would result in a coherent and comprehensive reform of the migration policy.
RETÓRICA DA AMEAÇA E SECURITIZAÇÃO: A política migratória dos Estados Unidos na administração Trump
Keywords: Immigration; Latinos; Muslims; Securitization; United states